KONSTRUKSI MAKNA RUQYAH BAGI PASIEN PENGOBATAN ATERNATIF DI KOTA PEKANBARU - Umi Dasiroh; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Ruqyah alternative treatment as a phenomenon becomes a very interesting study to be studied. Doing alternative treatment Ruqyah is not an easy thing, considering that alternative treatment Ruqyah is still classified as rare treatment when compared with medical treatment. Ruqyah in Peknbaru city is one of the favored treatment by pekanbaru society. But still many contradictions against alternative treatment Ruqyah in the city of Pekanbaru also affect the patient alternative medicine in interpreting the treatment that live. This study aims to determine the motives of alternative medical patinets in Pekanbaru city to do Ruqyah, knowing the meaning of Ruqyah that their live as well as their communication experience.This research uses qualitative research method with phenomenology approach. The subjects consisted of seven patients of Ruqyah alternative treatment in Pekanbaru City who were selected by using snowball technique. Data collection is done through in-depth interviews, observation and documentation. To test the validity of the data writer used the method of extension of participation and triangulation.The results of this study indicate the motive of alternative medical patients in Pekanbaru City Ruqyah consists of the motive of the past (because motive) and the motive of the future (in order to motive). The motive of the patient's past alternative treatment Pekanbaru doing Ruqyah is (1) obsessive motive (2) financial motive and (3) the background motive of the disease, while the future motive of patient of alternative medicine in Pekanbaru City doing Ruqyah is (1) (2) evaluation motives and (3) motive paradigm. Alternative medicine patients interpret the Ruqyah they live as (1) syariat in Islamic religion, (2) self-cleaning process and (3) solution for non-physical pain. The communication experience of alternative treatment patients in doing Ruqyah is divided into experience while undergoing treatment and experience after treatment. Based on the motives, meanings, and experiences of the patients on Ruqyah based on the frequency of recovery he gave birth to the types of alternative ruqyah treatment patients in pekanbaru city, namely the type of Ruqyah taqwa patient and Ruqyah future patient type.